1984
DOI: 10.1002/art.1780271013
|View full text |Cite
|
Sign up to set email alerts
|

Self‐associating igg rheumatoid factors in mrl/1 autoimmune mice

Abstract: Previous work has shown that the intermediate complexes isolated from the plasma of patients with rheumatoid arthritis are composed of self-associating IgG rheumatoid factors. Mice of the MRLh strain develop spontaneous autoimmune disease with arthritis that is pathologically similar to human rheumatoid arthritis. Also, the sera of MRL/I mice contain autoantibodies to nuclear antigens as well as IgM and IgG rheumatoid factors. The present studies were done to determine if the IgG rheumatoid factors isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…This was demonstrated by different methods proving the critical aggregation requirement for effective binding of these antibodies.The sensitivity for coat concentration, the high effectivity of solid-phasebound and heat-aggregated IgG2, and the intermediate activity of immune complexes formed at different antigen, antibody ratios as well as the lack of binding to cell surface IgG2, point to the critical steric orientation of multiple Fc portions which may favor binding of these mAb.These data are consistent with previous suggestions for the functional monovalency of the Fc region in binding to certain RF-type autoantibodies [47].…”
Section: Binding Of Biotinylated Mab To Cell Surface Igghsupporting
confidence: 93%
“…This was demonstrated by different methods proving the critical aggregation requirement for effective binding of these antibodies.The sensitivity for coat concentration, the high effectivity of solid-phasebound and heat-aggregated IgG2, and the intermediate activity of immune complexes formed at different antigen, antibody ratios as well as the lack of binding to cell surface IgG2, point to the critical steric orientation of multiple Fc portions which may favor binding of these mAb.These data are consistent with previous suggestions for the functional monovalency of the Fc region in binding to certain RF-type autoantibodies [47].…”
Section: Binding Of Biotinylated Mab To Cell Surface Igghsupporting
confidence: 93%
“…The histopathogenesis of these types of glomerular lesions in this strain of mice may possibly be considered to be under the control of multiple factors, including antigen specificities of antibodies, charge and/or sizes of circulating immune complexs, Ig isotypes, etc. [6][7][8][9]. We previously developed two nephritogenic IgG3-producing hybridomas from an unmanipulated MRL/lpr mouse, 2B11.3 and 7B6.8, which induced two different types of glomerular lesions when injected into SCID mice; an endocapillary proliferative and a wire loop-like lesion, respectively [10].…”
mentioning
confidence: 99%
“…Binding sites on IgG for both polyclonal and monoclonal RFs were previously localized to the interface of the heavychain C-region domains (CH) 2 and 3 by measuring RF binding to proteolytically cleaved fragments of IgG (12)(13)(14) and by performing competitive inhibition studies with staphylococcal protein A (SPA) (12,13), a protein known from x-ray crystallographic studies to bind IgG at the CH2-CH3 interface (15). By shuffling heavy-chain C-region exons between IgG4 and IgG3 and creating hybrid IgG4/IgG3 antibodies, we showed that the binding of monoclonal RFs to IgG4 and not IgG3 is attributable to sequence variation in CH3 (11).…”
mentioning
confidence: 99%